DESCRIPTION OF KNOWLEDGE, ATTITUDE, AND BEHAVIORAL BREASTFEEDING ON WORKING MOTHER IN THE ARJASA COMMUNITY HEALTH CENTER WORKING AREA IN JEMBER REGENCY - Fitri Al Vianita; Dini Kurniawati; Peni Perdani Juliningrum (Journal of Nursing Science Update (JNSU), 2020)
Exclusive breastfeeding is an effective way to prevent child mortality. One of the factors that become an obstacle in exclusive breastfeeding is the status of the mother who works, which affects the mother to give exclusive breastfeeding, especially if the mother doesn’t know about exclusive breastfeeding. The purpose of this study was to find out how the description of knowledge, attitudes, and behavior of exclusive breastfeeding on working mothers in the Arjasa Community Health Center Working Area in JemberRegency. This type of research is descriptive with a cross-sectional approach and use a purposive sampling technique. Data collection was finished using a questionnaire. Univariate analysis was used to determine the frequency and percentage of each subvariable. The results showed that 3% of working mothers have less knowledge, 3% have enough knowledge, and 61% have good knowledge. 16% of working mothers have enough attitude, 51% have a good attitude. Working mothers who gave exclusive breastfeeding as much as 40% and did not give exclusive breastfeeding as much as 27% of the total of respondents. Knowledge and attitudes towards exclusive breastfeeding cansupport mothers to give exclusive breastfeeding. Knowledge and attitude are not the only factors that influence exclusive breastfeeding, in this region the status of the work plays a greater role. Works can not be used as an excuse for the mother not to give exclusive breastfeeding. The rights and welfare of the mother have been guaranteed and protected by the Health Law and Labor Law